2016
DOI: 10.1007/s11751-016-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

The functional results of tibial shaft fractures treated with intramedullary nail compressed by proximal tube

Abstract: Nailing of tibial shaft fractures is considered the gold standard surgical method by many surgeons. The aim of this retrospective study was to investigate and compare the clinical outcome of tibial shaft fractures treated with intramedullary nails compressed by proximal tube and conventional intramedullary interlocking nails. Fifty-seven patients with tibial shaft fractures, treated with intramedullary nails compressed by proximal tube (n = 32) and the conventional interlocking nails (n = 25), were reviewed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…Intramedullary interlocking compression nails can reduce the length of the fracture union period in patients with tibial fracture. [9] In our study, the union period was much shorter in Groups 2 and 3 (compression) when compared with that of Group 1 (non-compression). No statistically significant difference was found between Groups 2 and 3 in terms of the length of the union period.…”
Section: Discussioncontrasting
confidence: 38%
“…Intramedullary interlocking compression nails can reduce the length of the fracture union period in patients with tibial fracture. [9] In our study, the union period was much shorter in Groups 2 and 3 (compression) when compared with that of Group 1 (non-compression). No statistically significant difference was found between Groups 2 and 3 in terms of the length of the union period.…”
Section: Discussioncontrasting
confidence: 38%
“…[21,22] The results of these studies showed that additional compression provides improved healing outcomes with less rate of non-union in transverse and oblique tibial shaft fractures. [21,22] The intended amount of compression can be achieved with ICN additive to the body weight in loaded state of walking. Active compression resists distraction forces in the unloaded state.…”
Section: Table IIImentioning
confidence: 99%
“…Tibia shaft fractures are major injuries and can result in severe permanent disability, such as mal-alignment and limb shortening, as well as amputation [2,3]. Based on the type of tibial fracture, whether closed or open, proximal to the knee joint or ankle joint, displaced or un-displaced, generally, infections, compartment syndrome, and non-union are other well-recognized complications of fractures of the tibia [2,4,5] The overall infection rate after surgical intervention of these injuries is about 1% -4% [6]. Deep infection rates range from 1% after surgical fi xation of closed low-energy fractures up to 30% in complex open tibia fractures [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally held in place by screws [2]. Intramedullary interlocking nails are very commonly used in trauma practice for tibial fractures, especially in the treatment of closed mid-shaft and Gustilo 1 fractures of the tibial [4] Intramedullary nailing of the tibial delivers consistently good results in terms of fracture union and functional outcomes, minimal surgical dissection with appropriate preservation of blood supply to the fracture [3]. Recent data suggest that early internal fi xation of closed long bone fractures is associated with improved outcomes, early weight bearing, less hospital stay, and early return to daily normal activities [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%